Study of the intra-variability of a person’s face from infrared images - Liao, Marc Zhi Xiong. (2010)
This is a report for the Final Year Project held in the final year of study of the u-year Electrical and Electronics Engineering course in Nanyang Technological University (NTU), starting in August 2009.